Le genre Eurysternus Dalman, 1824 (Scarabaeidae : Scarabaeinae : Oniticellini), revision taxonomique et cles de determination illustrees - Francois Genier (Pensoft Publishers, 2009)
Dung Beetles (Scarabaeinae) are recognized and used as one of the principal bioindicators of ecosystem health and classification. The genus Eurysternus is one of the dominant taxa of Scarabaeinae in the Neotropical region where they have a key impact on ecosystems. This book will allow for the easy identification of the 53 currently recognized species of this important genus through multilingual identification keys (French, English, Spanish and Portuguese), an extensive collection of illustrations (drawings, scanning electron micrographs and photographs) and color distributional maps. A complete taxonomic treatment of the genus and information on collecting methods, habitat and phenology are provided for all species. Data were compiled by the author from over 16 500 specimens studied.